2017
DOI: 10.1037/tra0000200
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory fear and helplessness predict PTSD and depression in domestic violence survivors.

Abstract: The findings support the contemporary learning theory of traumatic stress and are consistent with findings of studies involving earthquake, war, and torture survivors. They imply that trauma-focused interventions designed to overcome fear, reduce helplessness, and restore sense of control over one's life would be effective in PTSD and depression in domestic violence survivors. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…A traumatic stress response framework has frequently been used to conceptualize the link between IPV and depression: traumatic events such as domestic abuse can cause fear, stress, and feelings of helplessness, isolation, and powerlessness, which may lead to depression [ 86 , 88 92 ]. Salcioglu et al [ 93 ] found that the strongest predictors of depression and PTSD in IPV survivors were helplessness and fear due to a sense of ongoing threat to safety. It has been suggested that a chronic traumatic stress response, where a victim is subjected to ongoing abuse, may lead to alterations in affect and sense of self (i.e., the predominance of self-blame and depressive affect) [ 94 – 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…A traumatic stress response framework has frequently been used to conceptualize the link between IPV and depression: traumatic events such as domestic abuse can cause fear, stress, and feelings of helplessness, isolation, and powerlessness, which may lead to depression [ 86 , 88 92 ]. Salcioglu et al [ 93 ] found that the strongest predictors of depression and PTSD in IPV survivors were helplessness and fear due to a sense of ongoing threat to safety. It has been suggested that a chronic traumatic stress response, where a victim is subjected to ongoing abuse, may lead to alterations in affect and sense of self (i.e., the predominance of self-blame and depressive affect) [ 94 – 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the direct and negative consequences of such abuse are well-known [2–5]. However, what has not been assessed until now is the negative health consequences that the experience of IPV can have on the child of the mother experiencing the abuse.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has one of the highest rates of intimate partner or domestic violence in the world with 50% of all murders of women being by their intimate partners at a rate of 8.8 per 100,000 population [1]. Death is not the only consequence of intimate partner violence (IPV), with research showing that victims are also known to suffer from depression [2, 3], suicidal ideation [4], the development of chronic pain injuries [3], severe reproductive health outcomes [3], and are more susceptible to HIV infection [3, 5].…”
Section: Introductionmentioning
confidence: 99%
“…There could be multiple reasons for inaccurate perception of risk. Some people may under-estimate their risk because they have substance abuse problems (Vatnar, Friestad, & Bjørkly, 2017), or because a combination of factors such as PTSD, depression and fear prevent them from assessing their risk accurately (Salcioglu, Urhan, Pirinccioglu, & Aydin, 2017). Of course, an additional challenge in asking victims about their fear is that some victims do not co-operate with the police (e.g., Myhill, 2017).…”
Section: Structured Professional Judgment the Brief Spousal Assault mentioning
confidence: 99%